UI/UX Model of Personnel Information System at the Synod Office using Design Thinking Method - Dewi, Stefani Fransisca; Hartomo, Kristoko Dwi (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2025)
The GKJ Synod Office is the administrative center for the Javanese Christian Churches, managing several service units such as correspondence, licensing for institutions/foundations, finance, and publishing materials for spiritual development. The GKJ Synod Office still faces issues related to employee data management, requiring technology to help address these challenges. The research uses the Design Thinking method, as it focuses on a user-centered approach, understanding the problems and limitations of users to create designs that align with their needs. This study results in a User Interface (UI) and User Experience (UX) model for a web-based employee information system that can be adopted by synods of churches across Indonesia. System testing was conducted to measure user satisfaction with the design of the employee information system, using the System Usability Scale (SUS) method. The final result for the admin was 88, and for the superadmin, it was 91. Based on the SUS Score interpretation criteria, the resulting system design received a grade (A), an adjective rating of (excellent), and acceptability ranges (acceptable), indicating a high level of user satisfaction.